ARTISTS BELONGING TO THE KHIVA KHANATE (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis explores the intellectual and cultural contributions of the Khiva Khanate’s royal family during the 19th century, focusing on figures such as Muhammad Rahim Khan II (Feruz), Muhammad Yusuf Bayani, Ahmad Tabibiy, and Komil Khorezmi. These individuals played pivotal roles in developing literature, historiography, translation, and music, fostering a vibrant intellectual and artistic environment in Khiva. Their works helped preserve and expand Central Asian cultural traditions while integrating influences from Persian and Arabic literary and musical heritage. This study examines their contributions and their lasting impact on Uzbek cultural identity, literature, historical documentation, and classical music traditions.